COVID-19 symptoms, internet information seeking, and stigma influence post-lockdown health anxiety - Li, Qian; Yang, Xue; Wang, Xin; Zhang, Han; Ding, Ningning; Zhao, Wenqian; Tian, Wenwen; He, Jiankang; Du, Mingxuan; Hu, Haiyan; Zhang, Guohua (Frontiers in Psychology, 2023)
With the lifting of Zero-COVID policies in China, rapid transmission of the virus has led to new challenges for patients' health anxiety. This study aimed to evaluate the relationship between COVID-19 symptoms and health anxiety, as well as the mediation paths between them in individuals infected with COVID-19.A cross-sectional study was conducted in December 2022, following the relaxation of anti-COVID measures in China. A validated online questionnaire was used to collect data from COVID-19 patients on the number and severity of symptoms, health anxiety, internet health information-seeking behavior (IHISB), and perceived stigma. Structural equation modeling was used to examine the mediation model in which COVID-19 symptoms would affect health anxiety via IHISB and perceived stigma.Overall, 1,132 participants (women, 67.6%) were included, with a mean (SD) age of 28.12 (10.07) years. Participants had an average of seven COVID-19 symptoms, with cough (91.3%), nasal congestion (89.1%) and fatigue (87.8%) being the most common. The number and severity of COVID-19 symptoms, IHISB, perceived stigma, and health anxiety were positively correlated with each other after adjusting for covariates (r ranging from 0.10 to 0.81, all p < 0.05). IHISB (effect = 0.14, p < 0.001) and perceived stigma (effect = 0.04, p < 0.001) fully mediated the relationship between COVID-19 symptoms and health anxiety.Interventions for health anxiety reduction during and after pandemics should target improving the quality of online health information, enhancing individuals' online healthy literacy, and reducing stigma.